Molecular structures and vibrational frequencies for [PdX2(tdmPz)] (X = Cl-, SCN-): A DFT study - Treu-Filho, Oswaldo [UNESP]; Rocha, Fillipe V. [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Pinheiro, Jose C.; Utuni, Vegner H. S. [UNESP]; Kondo, Rogerio T.; Mauro, Antonio Eduardo [UNESP] (Elsevier B.V., 2009)
Theoretical molecular structures of the complexes [PdCl2(tdmPz)] (1) and [Pd(SCN)(2)(tdmPz)] (2) (tdmPz = 1-thiocarbamoyl-3,5-dimethylpyrazole) were investigated using B3LYP/DFT method. The new complexes were prepared and characterized by elemental analysis and IR spectroscopy. The calculated bond distances and angles indicated a square planar coordination polyhedron around the palladium center for (1) whereas complex (2) exhibited a slightly distortion in its square planar coordination environment. The theoretical infrared spectra of C, symmetry (electronic state (1)A) of the compounds are in agreement with the experimental data. The molecular orbital description HOMO and LUMO for compounds (1) and (2) were also described in this work. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: DFT calculation; Total atomic charges; Infrared spectroscopy; Palladium